Effect of crop growth regulation and defoliation on productivity and economics of summer greengram - Shyam, C.; Deol, J.S.; Kaur, Ramanjit (Annals of Agricultural Research, 2018)
Indeterminate growth habit of greengram causes inefficient partitioning of photosynthates, resultingin lower seed yield and higher stover yields. Interestingly, growth regulators have been used inmany studies to modify plant physiological processes and improve seed yields in pulses. Hence, afield study was conducted in Students Research Farm, Punjab Agricultural University, Ludhiana,during summer season of 2015, to assess the impact of one growth retardant and three defoliants onproductivity and economics of summer greengram. The treatments included mepiquat chloride,ethrel, thidiazuron applied alone or in combination and paraquat and unsprayed control. The resultsrevealed that yield and yield attributes were significantly affected by these growth regulationtreatments. Application of ethrel @ 1.0 l/ha at 55-60 DAS significantly improved yield and yieldattributes viz number of pods per plant, pod setting percentage and 100 seed-weight compared tocontrol. Path analysis of the yield attributes indicated that flowers per plant, pods per plant, podsetting, and 100 seed weight were significantly correlated with the seed yield.